WTO Agricultural Trade Battles and Food Aid - Jennifer Clapp (Third World Quarterly, 2004)
Recent agricultural trade battles at the WTO between the US and the EU have important implications for the Global South, in particular with respect to food aid. The current Doha round of trade talks hinges closely on agreement in the area of agriculture, and a key issue of disagreement between the US and the EU is the question of whether the WTO should impose disciplineson food aid and agricultural export credits. The US has also challenged the EUat the WTO over trade in genetically modified organisms (GMOs). The outcome of this dispute will affect food aid, as many countries have ent yearrejected GM food aid from the US on the grounds that it would harm their export markets in Europe. Decisions on both of these battles should be forthcoming within the next year or two, and the outcomes will affect food aid policies.